Kyrgyz Republic : Agricultural Policy Update, Volume 2. Main Report - World Bank (Washington, DC, 2013)
This policy note examines the policy and investment framework between 2003 and 2010, resulting sector performance and the priorities for future development. It draws attention to the need to refocus on completing the fundamental reforms and investments on which Kyrgyzstan's early successes were built. These include further development of land market, building rural finance markets, further public investment and institutional development in the irrigation sector, encouraging greater private investment in the seeds sector and machinery services, public-private partnerships for advisory service provision, completion of ongoing reforms in pasture management, development of veterinary services and improving the business environment for private investment in agro-processing. The policy Note discusses the government's approach to achieving greater food security, which centers on food self-sufficiency and discusses why this is not the best route to raising low rural incomes - the root cause of food insecurity. The report discusses some of the policies conceived after the food price crisis, including intervention in output markets, and argues that these are likely to be unaffordable, ineffective and will divert limited resources away from more important reforms. The policy note describes possible approaches to development of the sector, including minimal government intervention in markets, promoting responsibility for management of natural resources with communities, facilitating user contributions to infrastructure investments and the cost of services and provision of public services through private providers. These were the foundation of many of Kyrgyzstan's earlier successes but also respond to the new imperatives brought about by the 2010 political crisis, including the renewed urgency for growth and stability in the agricultural sector to rebuild rural communities, fiscal discipline to address the budget deficit and improved governance to restore confidence in government. The strategic objectives could more usefully emphasize the need to: a) raise rural incomes; b) protect vulnerable consumers from price and supply shocks; c) increase agricultural profitability and reduce risk; d) protect consumers from public health risks; and e) arrest environmental degradation and loss of biodiversity.